By-catch of sturgeon juveniles in beach seine fishing method in Mazandaran Province, northeast Iran - Moghim, M.; Fazli, H.; Khoshbavar Rostami, H.A. (2005)
In an attempt to recognize the harmful fishing times and locations for sturgeons, we used catch statistic to evaluate by-catch of sturgeon juveniles during beach seine fishing over the years 2001-2002 in Mazandaran Province. We found that over the fishing period, 23760 hauls were conducted during which 103000 sturgeons were caught. The highest by-catch occurred in October (37% of the catch) and the lowest occurred in January (5% of the catch). The maximum sturgeon catch per haul was 14.2 in autumn decreasing through the year with 1.26 sturgeon fish caught in each haul in spring. The species composition of the by-catch sturgeon juveniles was determined to be Persian sturgeon (54%), Stellatus sturgeon (37%), Beluga (6%), Russian sturgeon (2%) and Spiny sturgeon (1%).